PENGARUH PERMAINAN EDUKATIF BERBASIS LAGU DAN KARTU TERHADAP KEMAMPUAN MENGHAFAL PERKALIAN SISWA SEKOLAH DASAR - Sari, Rinta; Nurulaeni, Fitria (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of using card-based educational games and songs on improving the multiplication memorization skills of third-grade elementary school students. The underlying problem is students' low ability to memorize multiplication facts, which impacts their difficulty in completing advanced arithmetic operations. The research method used was a quasi-experimental design with a nonequivalent control group. The sample consisted of two classes: class IIIA as the experimental group, which received instruction using cards and songs, and class IIIB as the control group, which received conventional learning. The research instruments were multiplication memorization tests in the form of oral and short answer questions. The results showed that students in the experimental class experienced a more significant improvement in multiplication memorization skills compared to the control class. Therefore, it can be concluded that the use of card-based educational games and songs is effective in improving elementary school students' multiplication memorization skills.